Penerapan Kaidah Isti'arah dalam Al-Qur'an: Studi Kasus Surah Ibrahim Ayat 1 dalam Kitab Tafsir Al-Mishbah Karya Quraisy Shihab - Amalina, Faridah Nur; Ilham A, Moch. Arif; Kholid, Abd. (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
His study will examine how the rule of isti'arah is applied in Surah Ibrahim verse 1 as taught in the book Tafsir Al-Mishbah by Quraish Shihab. This study is critical because the rules of isti'arah in the science of balaghah play an essential role in increasing our awareness of the beauty of the language of the Qur'an and the divine meanings contained in it. Surah Ibrahim verse 1 was chosen as a case study because this verse includes a complex linguistic style, thus offering deep insight into the use of isti'arah in conveying deep spiritual meaning. This verse uses the metaphor of al-nur (light) to symbolize faith and divine guidance, whereas al-zhulumat (darkness) represents disbelief and error. This study uses a descriptive-qualitative method with a focus on textual analysis. Data was obtained through a literature review of the book Tafsir Al-Mishbah and other references relevant to the science of balaghah. The results of the study show that Quraish Shihab in Tafsir Al-Mishbah provides a profound interpretation of isti'arah by identifying that this verse not only beautifies the arrangement of words but also strengthens the message about the prophetic mission and divine values. Isti'arah in Surah Ibrahim verse 1 is an expressive tool that connects literal and figurative meanings to clarify moral and theological messages. This study shows that the balangha approach, especially the isti'arah principle, is critical in revealing the beauty and depth of the meaning of the Qur'an and is relevant for use in contemporary interpretation studies.